Machine learning-based clustering in cervical spondylotic myelopathy patients to identify heterogeneous clinical characteristics - Zhou, Chenxing; Huang, ShengSheng; Liang, Tuo; Jiang, Jie; Chen, Jiarui; Chen, Tianyou; Chen, Liyi; Sun, Xuhua; Zhu, Jichong; Wu, Shaofeng; Ye, Zhen; Guo, Hao; et al. (Frontiers in Surgery, 2022)
Abstract Background: Anterior cervical decompression and fusion can effectively treat cervical spondylotic myelopathy (CSM). Accurately classifying patients with CSM who have undergone Anterior Cervical Decompression and Fusion is the premise of precision medicine. In this study, we used machine learning algorithms to classify patients and compare the postoperative efficacy of each classification. Methods: A total of 616 patients with cervical spondylotic myelopathy who underwent Anterior Cervical Decompression and Fusion were enrolled. Unsupervised Machine Learning Algorithms (UMLA) were used to cluster subjects according to similar clinical characteristics. Then, the results of clustering were visualized. The surgical outcomes were used to verify the accuracy of machine learning clustering. Results: We identified two clusters in these patients who had significantly different baseline clinical characteristics, preoperative complications, the severity of neurological symptoms, and the range of decompression required for surgery. UMLA divided the CSM patients into two clusters according to the severity of their illness. The repose to surgical treatment between the clusters was significantly different. Conclusions: Our results showed that UMLA can be used to rationally classify a heterogeneous cohort of CSM patients effectively, and thus, it might be used as the basis for a data-driven platform for identifying the cluster of patients who can respond to a particular treatment method. Keywords: machine learning, anterior cervical discectomy and fusion, anterior cervical corpectomy and fusion, cervical spondylotic myelopathy, cluster analysis.